Implications of Smart Meter to Energy Competition - Lu, Chang Ling (2010)
Even though energy market has been opened up since 1999 in UK, many of the residential consumers are still locked-in with their former regional monopoly supplier. This is largely due to switching costs which are viewed as substantial in this industry and inhibit consumer from switching to other energy suppliers. Where switching costs do seem to distort competitive process, the mandate of rolling out smart meter in all Great Britain (GB) household by 2020 reduces the switching cost as part of its benefit to encourage consumers switching. This move by the government will cause an impact on energy suppliers as the industry will be more highly competitive. As such, the objective of this paper is to examine the impact of smart meter roll out that are likely to have on energy suppliers. This is achieved through identifying multiple switching costs dimensions in today energy industry and the determinants of customer retention. Findings in this study show that the main driver in consumer switching is cost savings. Consumers are looking for cost savings of £100-120 per year as a motivation to switch reflects substantial switching cost in the energy industry which require significant amount of reward to compensate them. Given that switching process is easy, most of the respondents will still choose not to switch if the savings from switching is not significant. This is because consumers also have to invest enormous effort and time in searching and comparing deals. Pricing uncertainty in the industry also makes it difficult for consumers to switch and has led to the attitude that switching energy supplier would not give them any gain as price difference is transitory. It has found that customer retention is also influenced by other factors such as tenure, experience in switching and demographic attributes. Though smart meter roll out reduces transactional costs in switching, energy suppliers could still determine the size of other switching costs dimensions to their advantage. Due to its strategic importance, this paper also offers a recommended framework developed for E.ON to effectively manage and utilise switching costs opportunities to create and sustain competitive advantage for the firm. However, it is unlikely competition alone would keep prices down and increase consumers‟ likelihood to switch for maximum gain available unless there is a change in customers‟ perception. Hence, the success of smart meter initiative is still significantly determined by consumer behaviour which drives industry performance.